THE DIFFERENCES BETWEEN MEN AND WOMEN LANGUAGE STYLES IN WRITING TWITTER UPDATES - FATIN, MARSHELINA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Fatin, Marshelina. 2013. The Differences between Men and Women LanguageStyles in Writing Twitter Updates. Study Program of English, UniversitasBrawijaya. Supervisor: Isti Purwaningtyas; Co-supervisor: Muhammad Rozin.Keywords: Twitter, Twitter updates, Language style, Men language, Womenlanguage. The language which is used by people has so many differences. The differences itself are associated with men and women which belong to gender. If there are differences in spoken language, written language also has differences among men and women especially in social networking site as it is connecting people all around the world through internet services. In this study, the writer is interested in investigating the differences of language style and different purposes in language use among men and women on twitter updates and also the purposesbehind it. The research problems of the study are (1) what kinds of language styles that are mostly used by men and women in writing twitter updates (2) what are the purposes of using certain language styles in writing twitter updates used by men and women on twitter.This study used qualitative approach. The data were the twitter updates written by men and women users on twitter. In analyzing the data, the writer used theories by Adelaide Haas (1979) and A. Mullac (2001). There were eight twitterusers consisting of four men and four women.The twitter updates of men and women users were mostly talking about the same language contexts: 1) Form: directive, expressive, the use of emoticons,slang and obscene words, and hyperbolic words, 2) Topic:  life-style, life’s trouble, human relation, and social life, 3) Content: positive and negative valuejudgment, 4) Use: assertiveness, argument, command, and request. However, their types and their aspects are found different. Men and women have different words choice. Men language form is found harsher while women language form is weaker and more polite. It means that, men and women still have their ownlanguage style because of the different types and aspects. In the communication purposes, the analysis shows that both men and women users on twitter mostly communicate or write twitter update to express feeling and opinion rather than the other communication purposes such as report fact, solving problem, and develop and maintain rapport.In short, the writer finds the language style and communication purposesbetween men and women twitter updates. The present writer suggests the futurewriters to find men and women differences in language style from literary workssuch as novel, short story, or next writers can examine other twitter feature such as twitter mention or also analyze the differences between men and women inconversation like in the movie or debate show on television. It is also suggestedfor the future writers to use another other theories beside Haas theory to analyze the phenomenon in sociolinguistic area especially in language and gender.